The incisal foramen as a means of insertion for one of three ultra-short implants to support a prosthesis for a severely atrophic maxilla – A short-term report. Issue 12 (December 2018) - Ewers, Rolf
Abstract: As a continuation of our prospective cohort study for a total of 18 patients with 72 implants in severely atrophic maxillae corresponding to Cawood and Howell class V and VI (1988) [1] with four 4.0 × 5.0 mm ultrashort locking taper implants Ewers et al., 2018 [2], we now present a prospective cohort study with a total of 9 patients. The special feature of this newly modified study is the reduction of the number of implants to only three 4.0 × 5.0 mm or 4.5 × 6.0 mm or 5.0 × 6.0 mm calcium phosphate-coated Bicon Integra CP implants. Reducing the number of implants is possible by inserting the middle implant into the incisal foramen and the nasopalatine canal. All patients were restored with metal-free prostheses made of a glass fiber-reinforced hybrid resin material. Neither were any implants lost during the observation period, nor did any patient experience any sensory alteration due to the placement of an implant into the nasopalatine canal. Three implants were sufficient in all patients to stabilize their 12-unit prosthesis.